Penentuan Rate Asuransi Kendaraan Bermotor Menggunakan Kredibilitas Bayesian - Dapa, Rahmila; Utami, Iut Tri (Indonesian Journal of Applied Statistics, 2023)
This paper uses Credibility to determine new rate based on data of historical claim in a motor vehicle insurance in Bandung, Indonesia. Rate is formed based on past loss through experience rating. Credibility is one of the examples of experience rating that considers group historical claims. One of the credibility methods is Bayesian credibility that considers rate as a random variable. Bayesian credibility is used based on claim frequency and claim severity from a group of policy holders in order to create new rates. In this paper, claim frequency followed the Poisson distribution while claim severity followed the Lognormal distribution. Result of analysis showed that rate values based on claim frequency and severity are higher than the rate values that were used back in 2010.Keywords: bayesian credibility; rate; claim frequency; claim severity